PELATIHAN NGRUKTI JENAZAH DI DESA SEPAT KECAMATAN MASARAN KABUPATEN SRAGEN: PELATIHAN NGRUKTI JENAZAH DI DESA SEPAT KECAMATAN MASARAN KABUPATEN SRAGEN - Ngatmin; Fatah Suparman; Mutia Azizah Nuriana; Desi Teri Saputri (LPPM STAIMAS WONOGIRI, 2023)
Death is a decree for every living creature, including humans. A Muslim who dies must be cared for as the Prophet Muhammad taught his people, namely ngrukti corpse. An important issue related to human relations with other humans when they have died is the problem of caring for or repairing a corpse, the body of a Muslim needs to be cared for because it is the right of the deceased and a collective obligation for Muslims who are still alive, or often called fardu khifayah. Therefore, assistance in the form of training to repair corpses for the community is considered very important. With this training, it is hoped that it can provide an understanding of the procedures for ngrukti corpses according to the sunnah of the Prophet, for community members in Sepat Village, Masaran District, Sragen Regency. The method used in this community service uses survey or observation methods, interviews, counseling, training and assistance to mosque and prayer room administrators. The result of the dedication was that the administrators of the mosque and mushala were quite enthusiastic about participating in the activities and had been able to practice how to bathe, shroud and pray for the corpse, while burying it had not yet been practiced.